Monitoring of glacier frontal parts on Galindez and Winter Islands (the Argentine Islands) in 2018—2019 years - Marusazh, Kh.I.; Hlotov, V.M.; Siejka, Z. (Український антарктичний журнал, 2019)
The work presents an analysis of climate variability and glaciological changes of the Antarctic Peninsula and the results of glacier monitoring on Galindez Island and Winter Island (the Argentine Islands in the Wilhelm Archipelago, Antarctic Peninsula) in 2018—2019. The main objective of research was to determine how the volumes of glaciers changed in 2018—2019 in the course of a complex study. У статті представлено аналіз кліматичних та гляціологічних змін Антарктичного півострова та результати моніторингу льодовиків на островах Галіндез та Вінтер (Аргентинські острови Архіпелагу Вільгельма, Антарктичний півострів) за період 2018—2019 рр. Метою роботи було визначення змін поверхневих об’ємів льодовиків на островах Галіндез та Вінтер за результатами комплексних досліджень за період 2018—2019 рр.